Experimental studies on convective heat transfer coefficient of water/ethylene glycol-carbon nanotube nanofluids. Issue 3 (23rd February 2020) - Baskar, S.; Chandrasekaran, M.; Vinod Kumar, T.; Vivek, P.; Karikalan, L.
ABSTRACT: The objective of the project is to study the enhancement of convective heat transfer of secondary refrigerants. It is the function of different volume fractions as well as different operating temperatures. This project deals with the use of CNT nanofluids with CNT as a nanoparticle and EG/water as a base fluid. In this study the theoretical study of CNT and thermo physical properties were reviewed and discussed. To investigate the convective heat transfer, an experimental set-up is required. The experimental set-up is used to compare the thermo physical properties of CNT nanofluids. Abbreviations: CNT: carbon nanotube; EG: ethylene glycol; MWCNT: multi-walled carbon nanotube